Non-mandatory say on pay votes and AGM participation: Evidence from Germany - Daniel Powell; Marc Steffen Rapp (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
Since August 2009, German legislation allows for voluntary Say on Pay Votes (SoPV) during Annual General Meetings (AGMs). We examine 1,169 AGMs of all German listed firms with more than 10,000 agenda items over the period 2010-2013 to identify (1) determinants and approval rates of voluntary SoPVs, (2) the effect of voluntary SoPVs on AGM participation, and (3) the effect of SoP on executive compensation. Our data reveals that in the first four years of the voluntary say on pay regime every second firm in our sample has opted for having a SoPV. The propensity for a SoPV increases with firm size, abnormal executive compensation and free float of shares. Indeed, smaller firms with concentrated ownership do not only have a lower propensity for a SoPV, but also show a higher propensity to opt for only limited disclosure of executive compensation. Approval rates of SoPVs are lower than the approval rate for the average AGM agenda item and this effect is stronger in (i) widely held firms as well as in (ii) firms with abnormal executive compensation. Additionally, SoPVs actually can increase AGM participation; however, this result is particularly evident for widely held firms. Finally, we find stronger pay for performance elements within total executive compensation, particularly when the effect of executive compensation is lagged over the years following the vote. Overall, our results are consistent with the view that firms use voluntary SoPV to gain legitimation for executive remuneration policies in firms with low ownership concentration. This is enforced, where (small) shareholders consider executive compensation a part of the agency problem of listed firms, and where (small) shareholders consider SoPVs as a possibility to actively influence corporate decisions, with these decisions leading to a higher degree of alignment between executive management boards and shareholders.
Keywords: G30; G38; J30; J33; 330; Corporate Governance; Executive Remuneration; Say on Pay; Annual General Meeting; Germany